Just transitions through digitally enabled sharing economies? - Affolderbach, Julia; Médard de Chardon, Cyrille (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
Digital technologies have become central to social interaction and accessing goods and services. Development strategies and approaches to governance have increasingly deployed self-labelled ‘smart’ technologies and systems at various spatial scales, often promoted as rectifying social and geographic inequalities and increasing economic and environmental efficiencies. These have also been accompanied with similarly digitalized commercial and non-profit offers, particularly within the sharing economy. Concern has grown, however, over possible inequalities linked to their introduction. In this paper we critically analyse the role of sharing economies’ contribution to more inclusive, socially equitable and spatially just transitions. Conceptually, this paper brings together literature on sharing economies, smart urbanism and just transitions. Drawing on an explorative database of sharing initiatives within the cross-border region of Luxembourg and Germany, we discuss aspects of sustainability as they relate to distributive justice through spatial accessibility, intended benefits, and their operationalization. The regional analysis shows the diversity of sharing models, how they are appropriated in different ways and how intent and operationalization matter in terms of potential benefits. Results emphasize the need for more fine-grained, qualitative research revealing who is, and is not, participating and benefitting from sharing economies.